Perspective Of Nigeria In The Twenty-First Century, Civil-Military Relations, Leadership, Nature And Character, And The Current Crisis Of Challenges - Abalaka, J.N; Ajiteru,S.A.R; Sulaiman T.H (International Journal of Humanities and Social Sciences Reviews, 2025)
This essay examines Nigeria's leadership dilemma and civil-military relations in the twenty-first century. The connections between the civilian authority (CAU) and non-governmental civilian organizations are known as civil-military relations (CMR) organizations (NGCG) against the military. However, peacebuilding is a strategy for fostering reconciliation and capacity building that aims to stop conflict or its resumption. The study looks at South West Nigeria's peacebuilding and civil-military relations from 2011 to 2018. The documentary research approach was used for this study, while content analysis was used to examine the work's content. Data for the research project was gathered through observation and documentary investigations. Agency theory is the theory used in this investigation. The results showed that: the military voluntarily accepts their subordinate status to the civilian authority or his representatives because of a constitutional provision that allows for their subordination to civilian authority; Additional results indicate that there was a bad peace between the military and non-governmental civilian groups because of the disputes between the two groups, which were centered on mass harassment and intimidation. The National Assembly should pass legislation requiring only former military personnel to serve as ministers of defense and police, respectively, according to the study's recommendations. Once more, the National Assembly should establish the Independent Monitoring Operation on Military (IMOM) from among non-governmental civilian organizations to keep an eye on troops' movements and actions. It should also have the authority to reprimand and sanction soldiers.